2020
DOI: 10.1016/j.amsu.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid dysfunction on hematological parameters: Case controlled study

Abstract: Introduction The thyroid gland has a very important role in hematopoiesis, blood disorders are frequently seen in patients with thyroid disorders. Thyroid hormones have direct effect on blood parameters by stimulating erythrocytes precursors and indirectly by enhancing erythropoietin production. Patients and methods This is a case-control study which included 300 subjects who were grouped to 3 equal groups as a control, hypothyroidism, and hyperthyroidism groups. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 17 publications
6
23
0
Order By: Relevance
“…The explanation may be due to lower levels of exercise and sunlight exposure and sequestering of 25-hydroxyvitamin D in adipose tissues. Our study showed lower serum 25-hydroxyvitamin D levels in obese patients and this difference was highly significant [ [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 90%
“…The explanation may be due to lower levels of exercise and sunlight exposure and sequestering of 25-hydroxyvitamin D in adipose tissues. Our study showed lower serum 25-hydroxyvitamin D levels in obese patients and this difference was highly significant [ [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, hyperthyroidism has been associated with low WBC counts [ 37 ]. THRA polymorphisms may influence energy metabolism and WBC production by modulating thyroid hormone activity [ 38 ]. LCT is an enzyme that converts lactose to glucose and galactose, and LCT deficiency induces lactose intolerance and is possibly involved in allergy by modulating immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the low levels of PTH after surgery have been proved to be associated with symptomatic hypocalcemia, authors recommend that more studies are still required to define the cut off level of the PTH which indicate medical treatment with either or both calcium supplementation and vitamin D. Other authors concluded that PTH may not be the only determinant for the development of hypocalcemia and other possible factors may play a major role like minerals, dietary habits, and other metabolic disorders [ [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%